Plurality and Cultural Specificity of Service Design in East and Southeast Asia
XII, 284 p. 82 illus., 62 illus. in color.
Keywords: This open-access book expounds on how service design has been adopted and practiced in Asia, and how it has impacted especially the East and Southeast Asian countries. As service design is a socio-technical practice that is co-produced in context, the contributors focus on how service design has been applied and how it has evolved heterogeneously by interacting with the cultural and social dimensions of Asian countries. As the application domains of service design vary, this book covers adoptions and practices in different areas: Asian governments, the civic and grassroots sector, and business transformation. The contextual framing of the chapters is ultimately synthesized and analyzed in the concluding Discussion chapter of the book. This chapter takes into consideration the history and objects of service design, the interactions between research and practice, methodologies, and comparisons to practices in the Western World. This book appeals to students, researchers, and professionals in the field. .